Multivariate Analysis on The Determinants of Work Fatigue Factors for Nurses Inpatient Care at RSUD Arifin Achmad Hospital Pekanbaru - Devi Purnama Sari; Tjipto Suwandi; Endang Purnawati Rahayu (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2020)
This research aims to analyze the relationship of age, sex, years of work, nutritional status and work shifts to work fatigue. This research is a quantitative observational analytic study with an analytic cross-sectional study design and a sample size of 60 people. Primary data were collected by direct observation, interviews with the KAUPK2 questionnaire and measurement of Lassidaya L77. The results of bivariate analysis showed a relationship between age and nurse work fatigue (p = 0.026). There was no gender relationship (p = 0.552), years of service (p = 0.104), nutritional status (p = 0.288) and work shift (p = 0.132) with work fatigue. Arifin Achmad Hospital (p = 0.009) POR 12,199 (95%: 1,847 - 80,575). Counfonding work shifts with tenure. There is no relationship between sex and nutritional status with the incidence of work fatigue. Nutritional status (p = 0.571), POR 1.458 (95%: 0.395 - 5.379). Nutritional status (p = 0.866) 1.062 POR (95%: 0.527 - 2.140). The age variable was not included in the multivariate analysis because it was homogeneous. From the results of the analysis it was concluded that the working period ≥ 10 years affects work fatigue compared to ten years <10 years.